2010
DOI: 10.1523/jneurosci.4272-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

CD200R1 Agonist Attenuates Mechanisms of Chronic Disease in a Murine Model of Multiple Sclerosis

Abstract: To assess the effects and mechanisms of a CD200R1 agonist administered during the progressive stage of a multiple sclerosis model, we administered CD200R1 agonist (CD200Fc) or control IgG2a during the chronic phase of disease (days 10 -30) in mice with experimental autoimmune encephalomyelitis (EAE), induced using myelin oligodendrocyte glycoprotein peptide 35-55 (MOG35-55) peptide. We found that administration of CD200Fc during the chronic stages of EAE reduced disease severity, demyelination, and axonal dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 45 publications
6
59
0
Order By: Relevance
“…Administration of a CD200R-blocking antibody to Lewis rats exacerbated EAE (63), and CD200-deficient mice experienced earlier onset of EAE, with increased microglia/macrophage accumulation and activation in the CNS as demonstrated by increased expression of inducible NOS (iNOS) (65). We found that administration of a CD200R1 agonist attenuated disease in a chronic MS model (66). Enhanced CD200 expression was associated with reduced Wallerian degeneration in the slow Wallerian degeneration (Wld s ) mouse (67), a spontaneously occurring mutant with the unique phenotype of protection against several forms of axonal injury (68)(69)(70)(71).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 80%
“…Administration of a CD200R-blocking antibody to Lewis rats exacerbated EAE (63), and CD200-deficient mice experienced earlier onset of EAE, with increased microglia/macrophage accumulation and activation in the CNS as demonstrated by increased expression of inducible NOS (iNOS) (65). We found that administration of a CD200R1 agonist attenuated disease in a chronic MS model (66). Enhanced CD200 expression was associated with reduced Wallerian degeneration in the slow Wallerian degeneration (Wld s ) mouse (67), a spontaneously occurring mutant with the unique phenotype of protection against several forms of axonal injury (68)(69)(70)(71).…”
Section: Immune Cells Involved In Neurodegenerationmentioning
confidence: 80%
“…While lack of CD200 signaling exacerbates neuroinflammation, enhanced CD200-CD200R signaling either via increased neuronal expression of CD200 or administration of the CD200R agonist CD200-Fc fusion protein, can down-regulate microglia activation, reduce pro-inflammatory cytokine expression and maintain neuronal integrity in the rodent experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis (MS) (Chitnis, et al, 2007, Liu, et al, 2010). Recent findings in human patients also support the role of CD200 in regulating microglia activation in neuropathological conditions.…”
Section: Microglia Escape From Neuronal Controlmentioning
confidence: 99%
“…Traditionally, a Percoll TM gradient has been used to remove cell debris and myelin from these dissociated adult CNS tissue preparations (Allen et al, 1993;Ford et al, 1995;Sedgwick et al, 1991). However, others have used a single 37% (v/v) Percoll TM step to isolate microglia and infiltrating leukocytes (Kivisakk et al, 2009;La Flamme et al, 2003;Liu et al, 2010;Salem et al, 2011). Percoll TM is a suspension of colloidal silica particles coated with polyvinylpyrrolidone (Pertoft et al, 1978).…”
Section: Q3mentioning
confidence: 99%